Effects of growth hormone treatment on adult height in severely short children with X-linked hypophosphatemic rickets - Meyerhoff, Nadine; Haffner, Dieter; Staude, Hagen; Wühl, Elke; Marx, Michaela; Beetz, Rolf; Querfeld, Uwe; Holder, Martin; Billing, Heiko; Rabl, Wolfgang; Schröder, Carmen; Hiort, Olaf; et al. (Pediatric nephrology, 2018)
BACKGROUND: We recently showed that a 3-year growth hormone (GH) treatment improves linear growth in severely short children with X-linked hypophosphatemic rickets (XLH). It is unknown if GH therapy increases adult height in XLH patients. - METHODS: We carried out a follow-up analysis of a randomized controlled open-label GH study in short prepubertal children with XLH on phosphate and active vitamin D treatment. The changes in SD scores (SDS) of height, sitting height, leg and arm length, and sitting height index (i.e., the ratio between sitting height and height) were analyzed in 11 out of 16 patients followed-up until adult height. - RESULTS: At baseline, XLH patients showed disproportionately short stature with reduced standardized height (-3.2 ± 0.6), sitting height (-1.7 ± 0.6), leg (-3.7 ± 0.7) and arm (-2.5 ± 0.8) length, and markedly elevated sitting height index (3.3 ± 0.6; each p < 0.01 versus healthy children). In GH-treated patients, adult height, sitting height, leg length, and arm length exceeded baseline values by 0.7 SDS, 1.7 SDS, 0.7 SDS, and 1.2 SDS respectively, although this was only significant for sitting height. In controls, no significant changes in linear body dimensions were noted. Adult height did not statistically differ between groups (-2.4 ± 0.7 vs -3.3 ± 1.2, p = 0.082). GH did not exaggerate body disproportion. - CONCLUSIONS: Growth hormone treatment did not significantly increase adult height in this group of short children with XLH, which may be at least partly due to the small number of patients included in our study.
Published: 20 October 2017
Gesehen am 09.04.2020